Task-Based Learning as an Instructional Strategy to Foster Speaking Skills in EFL Classrooms - Iwan Dudy Gunawan (Prominent, 2025)
Speaking is an essential ability in English as a Foreign Language (EFL) acquisition; nonetheless, it poses significant challenges for Indonesian university students due to restricted exposure, insufficient communicative practice, and the prevalence of traditional grammar-centric teaching methods. In addressing this issue, Task-Based Learning (TBL) has been suggested as a learner-centered and communicative methodology to enhance speaking fluency. This study examines the application of TBL in an EFL speaking class, assesses its effects on students' speaking sub-skills, and evaluates the attitudes of both students and lecturers concerning the model. The study utilized a mixed-methods approach with an integrated experimental framework. The study involved 58 English as a Foreign Language (EFL) students from a private university in Indonesia, categorized into a control and an experimental group. Data were gathered via pre-test and post-test speaking evaluations, classroom observations, student surveys, and instructor interviews. The TBL intervention was implemented in five cycles, following the phases of pre-task, task cycle, and linguistic emphasis. The results indicated substantial enhancements in all speaking sub-skills, with the most pronounced advancements noted in fluency and vocabulary. Observations demonstrated heightened student participation and interaction during activities, while survey findings reflected favorable student perceptions of TBL. Instructors noted increased student engagement but also emphasized difficulties in task formulation and classroom administration. This study validates the efficacy of TBL in improving speaking skills and provides insights for communicative language teaching methodologies in Indonesian higher education.Â